Rare case of removal of intrabiliary retained broken PTBD wire with redo-hepaticojejunostomy - Gupta, Monika (International Surgery Journal, 2019)
This is a rare case of surgical removal of intrahepatic retained broken wire of percutaneous transheaptic biliary catheter, which caused cholagitis and severe pain in a 59-year-old female who had undergone percutaneous transhepatic biliary dilatation of stricture hepaticojejunostomy in past. This is rare case ever reported of surgical removal of a broken PTBD wire retained inside left biliary system, post percutaneous transhepatic biliary dilatation of biliary stricture. Patient also underwent redo-hepaticojejunostomy for treatment of stricture hepaticojejunostomy in same sitting. This guidewire was put by interventional radiologist for dilatation of hepaticojejunostomy stricture. Patient had developed stricture in hepaticojejunotostomy which was done in year 2007 along with choledochal cyst excision by some other Gastrosurgeon. But one reoperation as well as one interventional approach had failed to retrieve the wire retained in biliary system. After that we successfully operated this challenging case and cured her of stricture hepaticojejunostomy, cholagitis and removed the foreign body in one surgery. Postoperatively we followed her up of 2 yrs. Patient is afebrile ,free of jaundice and has normal LFT on 2 yrs of follow up. Broken guidewire during percutaneous intervention in obstructed biliary system is an emergency as it acts as foreign body, removal with reansatomosis gives a fair chance of cholangitis free survival to patient.